Compreendendo os aspectos do ensino de geografia no regime militar brasileiro: retrocesso e apagão crítico? - Martins, Patrícia Pompeu [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This research focuses on the teaching of Geography during the Brazilian military period. It aimed to identify the academic studies that approach the thematic military regime and the teaching of Geography in Brazil; To elaborate a research instrument containing data on the teaching og Geography in the military period to support future research; And to initiate an approximation to the understanding of how the teaching of Geography was sent in the Brazilian military period. This is documentary and bibliographic research developed through localization procedures, meeting, Selection and analysis of documentary sources. It is concluded that despite the theoretical methodological progress achieved by academic Geography in the analyzed period, the teaching of the discipline in schools was marked, as the studies indicate, by the imposition of the curriculum and by the teachers' lack of freedom in the selection of teaching contents, These being more related to the descriptive and less critical aspects of the social and political conjunctures of the country

A presente pesquisa foca o ensino de Geografia durante o período militar brasileiro. Teve como objetivos identificar os estudos acadêmicos que abordam a temática regime militar e o ensino de Geografia no Brasil; elaborar um instrumento de pesquisa contendo dados sobre o ensino de Geografia no período militar para subsidiar pesquisas futuras; e iniciar uma aproximação ao entendimento de como o ensino de Geografia foi encaminhado no período militar brasileiro. Trata-se de pesquisa documental e bibliográfica desenvolvida por meio de procedimentos de localização, reunião, seleção e análise de fontes documentais. Concluiu-se que apesar do avanço teórico metodológico alcançado pela Geografia acadêmica no período analisado, o ensino da disciplina nas escolas foi marcado, conforme indicam os estudos, pela imposição do currículo e pela falta de liberdade dos professores na seleção dos conteúdos de ensino, sendo estes mais relacionados aos aspectos descritivos e menos críticos das conjunturas sociais e política do país
Keywords: Geografia - Estudo e ensino; Professores de geografia; Brasil - Historia - 1964-1985